Does forward looking Taylor rule forecast Indian data well? - Ghosh, T.; Parab, M. (International Journal of Academic Staff (IJAS – 2019), Volume 01, Issue 01. Department of Social Statistics, Faculty of Social Sciences, University of Kelaniya, Sri Lanka, 2019)
Forward looking Taylor rule bodes well for many inflation targeting economies. This paper looks at forecast accuracy and predictive efficiency of a forward looking Taylor rule for India especially after its adoption of flexible inflation targeting in 2015. Our analysis shows that a forward looking Taylor rule fits well for India, especially when augmented using an external benchmark like the exchange rate or the US monetary policy. Using generalized method of moments (GMM) technique a la Clarida et al (1998), we analyze the forecasting efficiency of the Taylor rule using three interest rates namely, weighted average call money rate (WACMR), 91-day treasury bills rate and 364-day treasury bills rate. The 364-day treasury bills rate provides the best estimate of Taylor rule. It is the only interest rate that is significantly influenced by the output gap. Reserve Bank of India (RBI) follows a forward looking Taylor rule during normal times. It deviates from the rule during crises as it did for Asian and global financial crises
Keywords: Monetary policy; Monetary policy reaction function; Taylor Rule